Melek Pendidikan Politik melalui Teknologi Internet di SMAN 1 Airpura Pesisir Selatan - Andri Rusta; Asrinaldi Asrinaldi; Tengku Rika Valentina; Hairunnas Hairunnas (Warta Pengabdian Andalas, 2023)
This activity aims to increase literacy through political education for novice voter students in using the internet wisely to participate in political life, thereby increasing knowledge about politics. The implementation of this activity was carried out in three stages: the first stage, namely the delivery of material through the lecture method; the second stage, namely training and modelling; and the third stage, namely post-training assistance by forming a politically intelligent community. Community service activities in outreach and training in political education in social media at SMA N 1 Airpura, Pesisir Selatan Regency, have been carried out well. The results of the activity were that this activity was attended by all elements of the school, namely SMA N 1 Airpura students, educators and teachers, school committees and other related elements. At the same time, the target audience for this service was 25 people who live in Airpura. Participants in this activity generally know about practical politics but need to learn how to be wise and intelligent in managing information about political issues on the internet, especially social media. Therefore, this group must continue to be accompanied so that political literacy among first-time voters and the younger generation can be realized in realizing political intelligence in Indonesia.